Construction of ceRNA and m6A-related lncRNA networks associated with anti-inflammation of AdipoAI - Yu, Hongwen; Wu, Hongle; Xie, Qiuyan; Liu, Zining; Chen, Zehao; Tu, Qisheng; Chen, Jake; Fang, Fuchun; Qiu, Wei (Frontiers in Immunology, 2023)
Adiponectin (APN) is an endogenous adipokine secreted from adipocytes that exerts anti-inflammatory properties. AdipoAI is an orally active adiponectin receptor agonist identified by our group that can emulate APN's anti-inflammatory properties through mechanisms that are not fully understood. LncRNAs, a type of noncoding RNA more than 200 bp in length, have been demonstrated to have abundant biological functions, including in anti-inflammatory responses. In the current study, we performed a lncRNA microarray in LPS-induced Raw264.7 cells that were prestimulated with AdipoAI and screened 110 DElncRNAs and 190 DEmRNAs. Enrichment analyses were conducted on total mRNAs and DEmRNAs, including GSVA, ssGSEA, GO/KEGG, GSEA, and PPI analysis. Among all these processes, endocytosis was significantly enriched. A coexpression analysis was built based on DElncRNAs and DEmRNAs. Then, using TargetScan and miRwalk to predict related microRNAs of DElncRNAs and DEmRNAs, respectively, we established competing endogenous RNA (ceRNA) networks including 54 mRNAs from 8 GO items. Furthermore, 33 m6A methylation-related marker genes were obtained from a previous study and used for the construction of an m6A-related lncRNA network by coexpression analysis. We identified FTO as the hub gene of the network and 14 lncRNAs that interacted with it. The expression levels of 10 lncRNAs selected from ceRNA and FTO-related lncRNA networks were validated with qRT‒PCR. Finally, macrophage phenotype scores showed that AdipoAI could attenuate the M2b and M2c polarization of macrophages and correlate with the above lncRNAs. Our work reveals that lncRNAs might be involved in the anti-inflammation process of AdipoAI in LPS-induced macrophages through the ceRNA network and the epigenetic regulation of m6A. Mechanistically, these lncRNAs associated with AdipoAI might be related to endocytosis and polarization in macrophages and provide new candidates for the anti-inflammatory application of APN and its receptor agonist.